2013
DOI: 10.1080/10962247.2013.793627
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and source identification of airborne particulate loadings at receptor site-classes of Lagos Mega-City, Nigeria

Abstract: Size segregated suspended particulate matter (PM2.5 and PM2.5-10) were collected using Gent low-volume air sampler at four different receptor site-classes in Lagos Mega City, Nigeria. The particulate mass loading was quantified and the concentration was analyzed to examine the pattern and variation from one receptor site-class to another. The PM2.5/PM10 ratio varied among the site-classes with the residential and marine sites having the least and highest ratio of 0.31 +/- 0.13 and 0.49 +/- 0.17 respectively. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…The result of this study however, agreed with the work of these other researchers in Nigeria with a PM 2.5 /PM 10 ratio below 0.5 [13][14][15][16][17].…”
Section: Temporal Variation Of Pm 25 /Pm 10 Ratiosupporting
confidence: 91%
“…The result of this study however, agreed with the work of these other researchers in Nigeria with a PM 2.5 /PM 10 ratio below 0.5 [13][14][15][16][17].…”
Section: Temporal Variation Of Pm 25 /Pm 10 Ratiosupporting
confidence: 91%
“…20 In some randomly selected Lagos levels of PM 2.5 and PM10 were 27 and 69μg/m 3 respectively. 21 In Abuja and Aba, the level of PM 2.5 was 14 μg/m 3 and 102 μg/m 3 while PM 10 level was reported as 38μg/m 3 and 553 μg/m 3 . The reports of Obioh et al 22 has revealed the PM 10 concentration of 38 μg/m 3 in Abuja and 553 μg/m 3 in Aba, and PM 2.5 concentration varying between 14μg/m 3 in Abuja and 102 μg/m3 in Aba.…”
Section: Discussionmentioning
confidence: 96%
“…In one of the studies at receptor sites in Lagos, Nigeria the PM levels were reported higher than the 150 µg/m 3 set by NAAQS. The authors reported between 150 and 240µg/m 3 for PM2.5 and 370-600µg/m 3 for PM10 (Owoade et al, 2013). Minka and Ayo (2014) documented that in harmattan period at the northern part of Nigeria, 400 -1200 kg/ha dust particles were deposited as compared to 100-400kg/ha in the Southern part.…”
Section: Regulatory Standards and Eventsmentioning
confidence: 97%